Proteomic Identification of Pathways Responsible for the Estradiol Therapeutic Window in AD Animal Models - Cui, Jie; Reed, Jon; Crynen, Gogce; Ait-Ghezala, Ghania; Crawford, Fiona; Shen, Yong; Li, Rena (Frontiers in Cellular Neuroscience, 2019)
Benefits and risks were reported for hormone therapy to prevent chronic disease, including Alzheimer’s disease (AD). While the Women’s Health Initiative (WHI) found no protective effect of hormone therapy on the cognitive function of women whose treatment was initiated far past the onset of menopause, other studies showed reduced risk of AD with midlife treatment, versus increased risk of AD with late treatment.These suggest a critical window during whichestradiol must be administered to prevent cognitive decline and AD in women.Our published work supports this, by demonstrating that early and long-term estradiol treatment improves cognitive function and reduce Aβ accumulation in AD mouse models with estradiol deficiency, while there is no effect of late and short-termestradiol treatment on AD neuropathogenesis. However, little is known about the molecular mechanisms underlying the criticalwindow and whether different protein networks are responsible for the brain estradiol deficiency-associated risk of AD in females. In this study, we used proteomics to identify target protein pathways that are activated during the estradiol therapeutic window in AD mouse model. Our results showed that different signaling pathways were involved in the regulatory effects of estradiol on MAP1A and hemoglobin α. Estradiol treatment increased the level of MAP1A through the phosphorylation of ERK1/2 and increased the level of hemoglobin α through the phosphorylation of AKT. This study has provided molecular insights into the “critical window” theory and identifies specific target proteins of therapeutic responsiveness that may lead to improved treatment strategies and optimal estradiol therapy.